Investigating Ideology Through Lexical Choice: A Critical Discourse Analysis of The Translated Novel“ The Dancer’ and The Original “ Ronggeng Dukuh Paruk” - Ahdi Riyono; Emzir Emzir; Ninuk Lustyiantie (JETL (Journal of Education, Teaching and Learning), 2018)
Translation has a crucial role in human life. It is viewed in different ways recently and theories of translation are more focused on factors that influence translators’ decision making.  Despite the importance of the ideology in translation, there is lack of research in this area, especially on literary translation.  This research tries to investigate the lexical choice in order to determine the ideology of the translator on literary translation. The researcher applied Fairclough approach focusing on experiential values; namely Classification Schemes and Ideological contested words which depict the text producer’s experience of the natural and social world. The result showed that lexical choices and manipulation were made due to linguistic and cultural differences. The translators selected similar vocabularies for representing the ideology of the original author. The translator also selected various translation strategies to make a meaning equivalent. They are phonological translation, borrowing, generalization, descriptive technique, contextual conditioning, cultural equivalent, and literal translation.